LQR CONTROL FOR A SMALL SCALE HELICOPTER IN HOVER FLIGHT CONDITION - Mochammad Ariyanto; Joga Dharma Setiawan; Maftukhin Ahmad (Prosiding SNST Fakultas Teknik, 2011)
Small scale helicopters have been used as unmanned aerial vehicle (UAV) because they have agility and maneuverability that make them as an ideal option for various missions ranging from weather research, agriculture, aerial surveillance to power line inspection. Small scale helicopter posses a higher bandwidth of dynamics and a greater sensitivity to control inputs which make them more difficult to control. This paper deals with the control system design using Linear Quadratic Regulator (LQR) for an autonomous small scale helicopter in hover flight condition. A nonlinear dynamics model of the small scale helicopter is derived from the Euler-Newton equations of motion. Linear model at hover flight condition is numerically extracted using MATLAB/Simulink. Linear control system is then designed for the small scale helicopter with the following predefined hover position and external disturbances such as longitudinal doublet input and gust. The Virtual Reality model in Matlab/Simulink is used to show the 3 D view of the simulation results. Kata kunci: LQR, hover, small scale helicopter,